Resilience in domestic urban development and planning - Pirisi, Gábor (POLARITIES, 2023)
The starting point of this study is the increasingly diverse use of the concept of resilience in social geography research. After the academic sphere and basic research, the concept has already appeared in Hungarian urban development. Larger Hungarian cities had to prepare sustainable urban development strategies that essentially rely on the concept of the resilient city. The study draws attention to the fact that, in addition to theoretical and conceptual problems, the development policy application raises a number of theoretical and practical problems related to the measurement of resilience and the monitoring of its “development”.